The start of a conversation on the value of New Zealand's financial/physical capital - John Janssen (New Zealand Government, The Treasury, 2018)
This discussion paper adds to the set of Living Standards Discussion Papers released in February 2018. Compared to the capitals covered in the February papers - human, natural and social - financial/physical capital is relatively more straight-forward given existing measurement frameworks such as the national accounts. The objective of the paper is to explain and assess the various indicators of financial/physical capital for the purposes of a Living Standards Dashboard. The paper looks at alternative definitions of financial and physical capital, the gaps relative to indicators proposed by the Organisation for Economic Cooperation and Development (OECD), and the measurement of capital. The most appropriate measure of capital depends on the purpose of the analysis, the required coverage, and the availability of data. For example, the capital measures used in a national balance sheet are not the same as the measures used in the analysis of productivity.
Keywords: 330